Pelaksanaan Kegiatan Market Day Dalam Upaya Menumbuhkan Jiwa Kewirausahaan Peserta Didik Paket A di PKBM Insan Cerdas Indonesia - Andriani, Salsabila Rizki; Lestari, Gunarti Dwi (J+PLUS UNESA, 2024)
Poverty remains a major problem in Indonesia. One of the influencing factors is the high unemployment rate among young people. To overcome this, there is a need for collaboration between the government and other stakeholders to create relevant skills training and education programs such as entrepreneurship education. Through entrepreneurship education, the government can prepare individuals to develop in the entrepreneurial field. One of them is through Market Day activities, students can practice various aspects of entrepreneurship such as planning, managing, and marketing products. In addition, Market Day is also a platform for building social skills such as communication, negotiation, and teamwork. This study aims to analyze the implementation of market day activities and describe efforts to foster the entrepreneurial spirit of package A students. This research focuses on the implementation of Market Day activities and their impact on the development of the entrepreneurial spirit of Package A students. This type of research is descriptive research with a qualitative approach. The data collection techniques used were in-depth interviews, participatory observation, and documentation. The data analysis used is the miles and huberman theory including data collection, data reduction, data presentation, and verification or conclusion drawing. The results showed that the implementation of market day activities at PKBM Insan Cerdas Indonesia proved effective in fostering entrepreneurial spirit, entrepreneurial interest, and teaching life skills for Package A students.